2014
DOI: 10.1093/hmg/ddu512
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identified SNP on 15q24 associated with bladder cancer risk in Japanese population

Abstract: Through genome-wide association analysis and an independent replication study using a total of 1131 bladder cancer cases and 12 558 non-cancer controls of Japanese populations, we identified a susceptibility locus on chromosome 15q24. SNP rs11543198 was associated with bladder cancer risk with odds ratio (OR) of 1.41 and P-value of 4.03 × 10(-9). Subgroup analysis revealed rs11543198 to have a stronger effect in male smokers with OR of 1.66. SNP rs8041357, which is in complete linkage disequilibrium (r(2) = 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 45 publications
(44 reference statements)
1
27
0
Order By: Relevance
“…Furthermore, genome-wide association studies (GWAS) have identified a subset of common variants associated with bladder cancer risk (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). However, these studies have primarily been conducted in individuals of European descent, and only one GWAS reported by Matsuda and colleagues had been performed in Japanese (14).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, genome-wide association studies (GWAS) have identified a subset of common variants associated with bladder cancer risk (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). However, these studies have primarily been conducted in individuals of European descent, and only one GWAS reported by Matsuda and colleagues had been performed in Japanese (14).…”
Section: Introductionmentioning
confidence: 99%
“…A small-scale case-control study has revealed the association of CYP2A6*1/*4 or *4/ *4 genotypes with decreased susceptibility to bladder cancer [48]; however, the relationship between CYP2A6 SNPs and bladder cancer risk has not been demonstrated by GWASs [1317]. Recently, Matsuda et al have reported that CYP1A2, another member of the CYP family of enzymes thought to metabolize tobacco-derived carcinogens, is associated with bladder cancer risk in Japanese population [18]. However, that study did not discriminate between non-invasive and invasive bladder cancers; therefore, CYP2A6 contribution to the risk of developing invasive bladder cancer phenotype could not be clearly determined.…”
Section: Discussionmentioning
confidence: 99%
“…Using candidate-gene approach, a previous study has demonstrated the association between an increased risk of bladder cancer and deletion of the GSTM1 gene on human chromosome 1p13.3, which is involved in the metabolism of carcinogens [12]. Many GWASs revealed a correlation between an increased risk of bladder cancer and single nucleotide polymorphisms (SNPs) [1318]. …”
Section: Introductionmentioning
confidence: 99%
“…We used UCSC Genome Browser to select SNPs within the gene region and SNPs flanking 500 bp of the gene boundary. (41,42). The standard protocol for genome-wide analyses was used for quality control (43).…”
Section: Selection Of Et-1 Pathway Candidate Genesmentioning
confidence: 99%